2021
DOI: 10.1038/s41598-021-01993-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of tear fluid amyloid and tau levels with disease severity and neurodegeneration

Abstract: There has been increasing interest in finding non-invasive biomarkers for neurodegenerative diseases such as Alzheimer’s disease (AD). This observational study investigated AD-specific biomarkers in tear fluid. Tear fluid was collected from a total of 65 subjects, including 23 patients with subjective cognitive decline (SCD), 22 patients with mild cognitive impairment (MCI), 11 dementia patients and 9 healthy controls (HC). Levels of amyloid-beta peptides (AB38, AB40, AB42), total-tau (t-tau) and phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Gijs et al measured Aβ 42 in tears using multiplex immunoassays and found the Aβ 42 levels changed with increasing AD stage with an area under the curve (AUC) of 0.725 [ 118 ]. Other Aβ peptides, Aβ 38 and Aβ 40 , were also detected in their subsequent study [ 119 ]. Recently, Wang et al developed a biosensor and detected variable Aβ 42 levels in different age groups of healthy participants [ 120 ].…”
Section: Novel Peripheral Body Fluid Biomarkersmentioning
confidence: 76%
See 1 more Smart Citation
“…Gijs et al measured Aβ 42 in tears using multiplex immunoassays and found the Aβ 42 levels changed with increasing AD stage with an area under the curve (AUC) of 0.725 [ 118 ]. Other Aβ peptides, Aβ 38 and Aβ 40 , were also detected in their subsequent study [ 119 ]. Recently, Wang et al developed a biosensor and detected variable Aβ 42 levels in different age groups of healthy participants [ 120 ].…”
Section: Novel Peripheral Body Fluid Biomarkersmentioning
confidence: 76%
“…Recently, Wang et al developed a biosensor and detected variable Aβ 42 levels in different age groups of healthy participants [ 120 ]. Gijs et al also analyzed T-tau, and its levels were also able to discriminate between AD patients and healthy controls with an AUC of 0.81 [ 118 , 119 ]. Quantitative proteomic results profiled that lipocalin-1, dermcidin, lysozyme-C, and lacritin can serve AD biomarkers [ 121 ].…”
Section: Novel Peripheral Body Fluid Biomarkersmentioning
confidence: 99%
“…In this regard, a recent study also suggested the potential of t-tau and Aβ42 markers at the lacrimal level for the diagnosis/discrimination of AD [ 130 , 131 ] ( Table 1 ). The authors determined a gradual increase in both biomarkers in tears throughout cognitive decline [ 130 , 131 ]. Additionally, Kenny and colleagues observed that the total tear concentration of microRNA-200b-5p was highly upregulated in AD samples compared to the control group [ 132 ].…”
Section: Ocular Alterations Related To Admentioning
confidence: 95%
“…Both t-tau and p-tau showed no differential expression among the three patient groups [ 129 ]. Moreover, the association of tear amyloid and tau levels with AD severity and neurodegeneration was also studied, highlighting the potential of tau and Aβ proteins in tear fluid as markers of AD severity [ 130 , 131 ]. In this regard, a recent study also suggested the potential of t-tau and Aβ42 markers at the lacrimal level for the diagnosis/discrimination of AD [ 130 , 131 ] ( Table 1 ).…”
Section: Ocular Alterations Related To Admentioning
confidence: 99%
See 1 more Smart Citation